Pengaruh Media Pembelajaran Interaktif Menggunakan Google Sites Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di SMK Auto Matsuda - Solihah, Ema Munawaroh; Janah, Hifni Fitriah Nur (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Low student learning outcomes in the Informatics subject at SMK Auto Matsuda highlighted the need for more interactive learning media. This study aimed to determine the impact of using Google Sites an interactive learning medium on student learning outcomes in Informatics. A quantitative approach was employed using a pre-experimental, one-group pretest-posttest design. The sample consisted of 34 students from the Grade X TJKT class, selected via purposive sampling. Data analysis involved descriptive statistics, a normality test, a paired sample t-test, and N-Gain analysis. The results showed an increase in average learning outcomes following the use of Google Sites, rising from 48.82 in the pretest to 76.76 in the posttest an increase of 27.94 points. The paired sample t-test yielded a significance value of 0.001 (p < 0.05), indicating a significant difference in learning outcomes before and after using Google Sites. The N-Gain score of 0.5673 fell into the medium category. Thus, the use of Google Sites demonstrated a positive influence on improving student learning outcomes in the Informatics subject at SMK Auto Matsuda.